Validation and Development of Magnetic Field Interactive Multimedia Using Adobe Flash as Physics Learning Media - Sabani, Ririn; Rahmad, M.; Nor, M. (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This research aimed to design and build interactive multimedia on the magnetic fieldâs topic using Adobe Flash as a physics learning media in Senior High School. The type of product is a validation of multimedia interactive. This research is an R&D research using ADDIE models. The data needed for this research are the validation assessment score given by the validatorswho are using evaluation sheets with descriptive analysis techniques. Validator consists of 4 experts as an expert construct and 3 experts as an expert user who given the score of the aspectthat is design, pedagogy, learning content, and users. The final results of the validation assessment of expert constructs are 3.49 with categorized as very high and the result of expert users are 3.59 with categorized as very high. The interactive multimedia had been declared valid and eligible for use in the process of learning and teaching in school.